Obesity in Adolescents: Prevalence and Association with Sociodemographic and Lifestyle Factors - Jain, Bhavna; Jain, Seema; Mittal, Chhaya; Chopra, Harivansh; Chaudhary, Parul; Bargayary, Harimu; Singh, Ganesh; Garg, Sunil K (Indian Journal of Community Health, 2023)
Introduction: Overweight and obesity has become a worldwide epidemic and is a growing public health concern. The increase in prevalence and severity of obesity among children and adolescents has been attributed largely to behavioral factors such as changing eating habits and sedentary lifestyles. Objective: To determine prevalence of obesity and abdominal obesity among adolescents and its association with sociodemographic factors and lifestyle. Methods: Present cross-sectional study was conducted in the urban field practice area under the Community Medicine Department of LLRM Medical College, Meerut, among 872 adolescents. All localities in the field area were covered and house to house survey was done. Questions were asked about eating patterns, physical activity and sedentary lifestyle. Data was collected and analyzed using appropriate statistical tests. Results: The prevalence of overweight and obesity was 17.43, 6.88%, respectively. Obesity was significantly higher among females, those who indulged in unhealthy eating habits were physically inactive, watched television for a longer duration and ate junk while watching television. Conclusion: In the present study, we found that high junk food consumption and a sedentary lifestyle were found to be significantly associated with childhood overweight/obesity. As a result, timely interventions should be taken to improve awareness about healthy lifestyle behavior to prevent obesity and its complications among adolescents.